2007
DOI: 10.1002/ejoc.200600883
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Synthesis of 7,8‐Dihydropyrimido[5,4‐d]pyrimidines

Abstract: Keywords: Cyanopurines / Amines / Rearrangement / Pyrimido [5,4-d]pyrimidines 7,pyrimidines 4 were isolated in very good yields by treatment of 9-aryl-6-cyanopurines 1 with primary amines. Nucleophilic attack of the amine on C8 of the purine ring was followed by ring-opening of the imidazole unit, and subsequent intramolecular cyclization involving the newly formed amidine group and the cyano substituent in the pyrimidine ring produced the 7,8-dihydropyrimido[5,4-d]pyrimidine structure 4. When ammonia was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Our studies [21,34] showed that nucleophilic attack of the amine to C8 of the purine ring was the first step of the cascade process leading to the formation of pyrimido-pyrimidine 2 through an ANRORC type mechanism (Scheme 1). Compounds 2 were isolated in very good yield, although in some cases the rearrangement product 3 could also be identified as a minor product.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Our studies [21,34] showed that nucleophilic attack of the amine to C8 of the purine ring was the first step of the cascade process leading to the formation of pyrimido-pyrimidine 2 through an ANRORC type mechanism (Scheme 1). Compounds 2 were isolated in very good yield, although in some cases the rearrangement product 3 could also be identified as a minor product.…”
Section: Resultsmentioning
confidence: 94%
“…[12,16,17] The 6-cyanopurines were also used as precursors of the pyrimido [5,4-d]pyrimidines by reaction with an amine. [3,4,6,[18][19][20][21] To the best of our knowledge, pyrimido [5,4-d]pyrimidine N-oxides were never reported in the literature. However, pyrimidine N-oxides are known.…”
Section: Introductionmentioning
confidence: 99%
“…6-Cyanopurines 1 had been previously used to generate 6-imidatopurines 6, 12 and reaction of these compounds with hydrazides was carried out in the presence of acid catalysis, aiming to prepare the 6-amidinopurines 4. Previous results on the reactivity of the purine ring, under basic conditions and in the presence of nucleophiles, indicated that attack on C8 was the major pathway, [8][9][10] leading to pyrimidopyrimidines 2. The use of a catalytic amount of sulfuric acid, when a suspension of compound 6a in dimethylsulfoxide was combined with acetic hydrazide 7a, prevented the competitive formation of product 2.…”
Section: Figure 1 a New Class Of Antitubercular Agentsmentioning
confidence: 97%
“…7 This approach has been used in our group for the efficient synthesis of compounds 2 (Scheme 1). 4,[8][9][10] According to the literature, structure 2 can be used to generate the aromatic analogue 3 by Dimroth rearrangement, in the presence of acid or base catalysis. 11 Furthermore, our studies on the reactivity of the pyrimidopyrimidine derivatives 2 (R 2 = OBn) have proved that the conversion of 2 (R 2 = OBn) into 3 (R 2 = OBn) occurs efficiently under acid conditions although other products may also be formed (Scheme 1).…”
mentioning
confidence: 99%
“…80 Furthermore, 9-substituted-9H-purine-6-carbonitriles 167 were used as synthetic intermediates for the synthesis of pyrimido [5,4-d]pyrimidine analogs 168 by reaction with various amines through ring transformations (Scheme 41). 14,24,[81][82][83][84][85][86][87][88][89] A series of pyrimido [5,4-d]pyrimidines 170 were prepared by reaction of 9-substituted-9H-purine-6-carbonitriles (167) with various hydrazides 169 by treatment in DMSO and water using catalytic DBU. Compound 170d was obtained by the reaction of 9-aryl-9H-purine-6-carbonitriles 167 with acetohydrazide (169c) in acetonitrile instead of DMSO and compounds 170k and 170o were prepared in ethanol (Scheme 42).…”
Section: Introductionmentioning
confidence: 99%